Imaging of Electrode Position after Cochlear Implantation with Flat Panel CT. (4th December 2012) - Arweiler-Harbeck, Diana; Mönninghoff, Christoph; Greve, Jens; Hoffmann, Thomas; Göricke, Sophia; Arnolds, Judith; Theysohn, Nina; Gollner, Ulrich; Lang, Stephan; Forsting, Michael; Schlamann, Marc
Abstract : Background . Postoperative imaging after cochlear implantation is usually performed by conventional cochlear view (X-ray) or by multislice computed tomography (MSCT). MSCT after cochlear implantation often provides multiple metal artefacts; thus, a more detailed view of the implant considering the given anatomy is desirable. A quite new method is flat panel volume computed tomography. The aim of the study was to evaluate the method's clinical use. Material and Methods . After cochlear implantation with different implant types, flat panel CT scan (Philips Allura) was performed in 31 adult patients. Anatomical details, positioning, and resolution of the different electrode types (MedEL, Advanced Bionics, and Cochlear) were evaluated interdisciplinary (ENT/Neuroradiology). Results . In all 31 patients cochlear implant electrode array and topographical position could be distinguished exactly. Spatial resolution and the high degree of accuracy were superior to reported results of MSCT. Differentiation of cochlear scalae by identification of the osseous spiral lamina was possible in some cases. Scanning artefacts were low. Conclusion . Flat panel CT scan allows exact imaging independent of implant type. This is mandatory for detailed information on cochlear electrode position. It enables us to perform optimal auditory nerve stimulation and allows feed back on surgical quality concerning the method of electrode insertion.